Utilization of waste fish bone as catalyst in transesterification of RBD palm oil - Abd Manaf, Intan Shafinaz; Cheong, Jiun Yi; Ab. Rahim, Mohd Hasbi; Maniam, Gaanty Pragas (Elsevier, 2019)
Biodiesel is becoming more important as it is chosen to be one of the alternative fuels to replace fossil fuel nowadays, as well as waste materials also play a significant role in cheaper and greener fuels. In this research, waste fish bones modified with potassium hydroxide (KOH) were utilized as a cost-effective catalyst in the transesterification of RBD palm oil with methanol. The waste fish bones were calcined at 900 ℃ for 2 h and then added with different concentration of KOH to form K+ impregnated calcined fish bones (K-CFB). The prepared catalysts were characterized by X-ray diffraction (XRD), field emission scanning electron microscopy-energy dispersive X-ray (FESEM) and thermogravimetric analysis (TGA). The characterization results showed that K+ was successfully impregnated on calcined fish bones (CFB). Methyl ester was yielded at the highest content of 96.14 wt. % when the conditions are optimized at 5 wt. % catalyst loading, methanol to oil ratio of 12:1 and reaction time of 3 h. The CFB loaded with 10 wt. % KOH (10K-CFB) was found to be a potential heterogeneous base catalyst for transesterification due to its high catalytic activity.